Unsur Tokoh Dan Penokohan Dalam Naskah Film Pendek Tilik - Naufal Zaky Afthony (Journal Proxemics, 2025)
The research entitled character analysis and depiction of characters in the drama "Tilik" by Bagus Sumartono was inspired by the emergence of criticism of society. The purpose of this research is to analyze the characters and the way these characters are described in the script. The author concludes that the characters shown reflect the lives of people who spread gossip without knowing the truth of the information being spread. The method used in this research is qualitative descriptive analysis. Data is collected through reading, analyzing and marking text or sentences related to characters and character depictions, this is done so that the characters in this short film are easier to study and apply in the social lives of readers. With this research, readers are expected to be able to apply the results in their social lives and not easily believe information without understanding the real truth. The findings of this research show that there is social criticism that triggers conflict, which is caused by things that have an impact on people's lives. Bagus Sumartono created various characters for each character, and the author succeeded in conveying the realities that exist in everyday life.